A Review on Implications of Physiotherapy Techniques in COPD: A Review Article - Arslan Saeed, Muhammad Umer Arshad, Wajeeha, Muhammad Usman Khalid, Amna Shahid, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To provide a review on the implications of different physiotherapy techniques for improving breathing patterns, lung capacities and volumes for management of Chronic Asthma COPD patients. Methodology: It was review on physical therapy interventions and results were formatted based.All the Randomized clinical/controlled trial published in last 5 years was selected. To trace articles, article searching was executed electronically using the following search terms: “Physiotherapy interventions”, “Asthma” and Medical Subject Headings (Mesh) on the following databases: PubMed and Web of Science. Only the full text available were selected and documented as per PICOS (Population, Interventions, Comparators, Outcomes, Study designs) model and PEDro Scale. Results: 1,594 articles were traced. After the application of inclusion and exclusion criteria, only 21 studies were analysed. Out of them16 were evaluated as physiotherapy intervention for asthmatic patients. Conclusion: The results evaluated by this study suggested that physical therapy provides an extensive choice of treatment for asthma patients and all of them shown improvements in quality of life and clinical symptoms. Different protocols of physiotherapy provide a massive range of variety of rehabilitation for asthmatic patient to cope with this situation and make them under control. Keywords: COPD, physiotherapy technique, PICOS, asthma